Algeria’s relationship with the Islamic world in French colonial policy - Charikhi, nabil (The Algerian Historical Journal, 2026)
This article attempts to address Algeria's relationship with the Islamic world during the French occupation, tracing the French occupier's stance and policy towards the cultural ties that linked Algeria to its surroundings in the Islamic East and West. This allowed us to understand the nature of colonial policy towards it, which was characterized by duality on the part of the occupier, as it exploited this relationship to serve its colonial policy and objectives, while oppressing Algerians who had connections with their Islamic world, either to practice their religious rituals, especially in the Hijaz, or to travel there to learn from its scientific institutions, such as the Zaytuna Mosque in Tunis and Al-Azhar University in Egypt.